Himalaya Frontier in historical perspective - Ray, N. R. (Nisith Ranjan), 1911-; Institute of Historical Studies (Calcutta, India); Seminar on the Himalaya Frontier (1979 : Gangtok, India) (Calcutta : Institute of Historical Studies, 1986)
Papers presented at the Seminar on the Himalaya Frontier, Gangtok, 1979, organized by the Institute of Historical Studies.
Includes bibliographies.
Keywords: Himalaya Mountains Region -- History -- Congresses